Cerebral Erdheim-Chester disease: report of two cases with progressive cerebellar syndrome with dentate abnormalities on magnetic resonance imaging. Issue 4 (1st October 1998) - Pautas, Eric; Chérin, Patrick; Pelletier, Sophie; Vidailhet, Marie; Herson, Serge
Abstract : Two patients with Erdheim-Chester disease with progressive cerebellar dysfunction and pyramidal signs are reported on. Cerebral MRI showed bilateral increased signal intensity in peridentatal regions on T2 weighted sequences. Both patients had kidney and bone involvement, established on bone biopsy for one. One patient improved with steroid therapy. This contrasts with previous reports, which describe rare neurological manifestations and the failure of different therapeutic approaches.